CERITA YAJID CILAKA: TRANSFORMASI TEKS SASTRA SYI’AH – SUNNI DI JAWA ABAD XIX - Abdullah Maulani; Rahmatia Ayu (Balai Penelitian dan Pengembangan Agama Jakarta, 2019)
This paper examines the transformation of texts that occurred in a text entitled Cerita Yajid Cilaka (CYC) NB 199 collection of the National Library of the Republic of Indonesia. This text is an adaptation of a popular classical Malay story, Hikayat Muhammad Hanafiyah (HMH), a text laden with Shi'a - Persian traditions and in its development this text was copied in various regions including Java and Ambon version which entitled Hikayat Khalifah Abu Bakar, Umar, Usman and Ali (HKAUUA). Using a comparative literary approach, researchers conclude that this text is acceptable among Sunni readers by experiencing various kinds of transformation. Starting from structural transformation to cultural transformation. In addition, these transformations are also related to the ideology of copyists who adhere to the Sunni orders.